Implementation of Interactive Workshops with Mentimeter, Crossword Puzzle, and Wordwall in the Professional Development of Teachers at SMAN 1 Sajingan - Sulistyarini Sulistyarini; Imran Imran; Ika Rahmatika Chalimi; Stella Pransisca; Yusawinur Barella; Venny Karolina; Edwin Mirzachaerulsyah; Hendra Hendra; Vionaria Vionaria; Fajar Adilah Pratama (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Faculty of Teacher Training and Education, Tanjungpura University, carried out community service entitled